Uwarunkowania sprawnego funkcjonowania rynku pieniężnego - Pauka, Marek (Conditions of Efficient Functioning of Money Market, 2005)
Money market as an essential component of the financial system consists of many segments. Each one plays an important role in the economy. It runs efficiently if some conditions are fulfilled. This is the subject of the paper.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 13-20